An Analysis of Early Childhood Bilingual Program Implementation at Happy Hive Kindergarten, Malaysia - Muthmainnah, Tsabita; Jayadinata, Asep Kurnia; Justicia, Risty; Ardhiyanti, Dhea; Mustafa, Lily Muliana (Journal of Languages and Language Teaching, 2025)
In the era of globalization, proficiency in international languages is a key factor for competitiveness and cross-cultural collaboration. Malaysia stands out as a significant global example by integrating bilingual education into the National Preschool Standard Curriculum (Kurikulum Standard Prasekolah Kebangsaan—KSPK) from the preschool level. This study analyzes the regulations, implementation, and challenges of the bilingual program at Happy Hive Malaysia as a learning model relevant to international contexts.Using a qualitative case study approach, data were collected through interviews with two educators, participatory observations, and documentation, then analyzed thematically. The main findings reveal that KSPK provides a strong foundation for early childhood language education, while Happy Hive successfully implements a balanced bilingual approach supported by interactive methods and educational media. The challenges encountered—including variations in children’s language proficiency, speech delays, and limited resources—were addressed through teacher training and adjustments to teaching methods. This study underscores the importance of curriculum integration, teacher competence, and child-centered methods for the success of bilingual programs. Policy recommendations include strengthening regulations, providing continuous teacher training, and enhancing support for bilingual resources and media. For practitioners, adaptive strategies and innovative learning media are suggested to improve the effectiveness of bilingual education, positioning Malaysia’s experience as a valuable reference for other countries.